Factors influencing hand washing behavior among food handlers in food service operations of boarding schools - Suhairom, Nornazira (2011)
Food poisoning outbreaks in schools have been linked to inadequate or lack of hygiene practices. Most reported food poisoning occurred in education and learning institution premises such as school canteens, hostels and dining halls of higher learning institution. The study aims to examine factors that relate and contribute to the hand washing behavior among food handlers in the food service operations of boarding schools. The variables studied were knowledge, attitude, subjective norms, descriptive norms, perceived behavioral control, barriers, intentions and behavior of hand washing. This study utilized an extended Theory of Planned Behavior with the addition of descriptive norms and barriers constructs. The instrument employed in this study was adapted from the instrument used in the studies which also measures people’s behavior using the Theory of Planned Behavior. This study involved 146 food handlers who work in 18 hostels kitchen from two types of boarding schools in Peninsular Malaysia which are Sekolah Berasrama Penuh (SBP) and Sekolah Menengah Kebangsaan Agama (SMKA). Cluster-stratified sampling was applied in this study. Findings revealed that most respondents had good knowledge with score ≥ 70% (84.9%). There was no significant differences between food handlers who had received formal food hygiene training with those who had not receive any formal training. Demographic characteristic, namely age, were found to have a significant differences in food handlers’ perceived behavioral control and behavior. There were significant relationships among perceived behavioral control, attitudes, descriptive norms and subjective norms towards intentions. Findings also show that there are significant relationships exist between behaviors and perceived behavioral control as well as between behaviors and knowledge. Findings indicated that attitudes, subjective norms and perceived behavioral control were positively contributed to the intention. About 20.9% of the variance in hand washing intentions could be predicted by these constructs. Intentions and perceived behavioral control contributed to the prediction of behaviors. About 9.1% of the variance in hand washing behaviors could be predicted by these two constructs. This study suggests that there is a need to improve the existing food handlers training and education in order to improve the practice of hand washing by the food handlers in the food service operations.